Effect of the Epoxide Contents of Liquid Isoprene Rubber as a Processing Aid on the Properties of Silica-Filled Natural Rubber Compounds - Gyeongchan Ryu (Polymers, 2021)
In this study, we examined the feasibility of using epoxidized liquid isoprene rubber (E-LqIR) as a processing aid for truck and bus radial (TBR) tire treads and investigated the effects of the epoxide content on the wear resistance, fuel efficiency, and resistance to extraction of the E-LqIRs. The results confirmed that, compared to the treated distillate aromatic extract (TDAE) oil, the E-LqIRs could enhance the filler–rubber interactions and reduce the oil migration. However, the consumption of sulfur by the E-LqIRs resulted in a lower crosslink density compared to that of the TDAE oil, and the higher epoxide content decreased the wear resistance and fuel efficiency because of the increased glass-transition temperature (Tg). In contrast, the E-LqIR with a low epoxide content of 6 mol% had no significant effect on the Tg of the final compound and resulted in superior wear resistance and fuel efficiency, compared to those shown by TDAE oil, because of the higher filler–rubber interactions.